Kualitas Pelayanan Pengujian Kendaraan Bermotor (PKB) Studi Kasus Pelaksanaan PKB Di Dinas Perhubungan Kota Payakumbuh - Rahmawati, Trisna (CV. ITTC INDONESIA, 2022)
The facts found in the initial research were that in the implementation of motor vehicle testing services at the Payakumbuh City Transportation Service there were problems in the form of shortages of human resources and testing equipment. So this study aims to determine and analyze the quality of PKB services at the Payakumbuh City Transportation Office. This research is a qualitative research using a case study approach. Using the theory of Parasuraman used to measure the quality of a service based on an analysis of Realibility, Responsiveness, Assurance, Empathy and Tangibles.